The effect of burn severity on functional capacity in patients with burn injury - (:unkn) unknown (IOS PRESS, 2019)
BACKGROUND: Burns are traumatic injuries that result in severe tissue damage. A reduction in exercise capacity is the most common functional impairment, although it is not clear to what extent the severity of the burn injury affects the exercise capacity. OBJECTIVE: The aim of this study was to examine the physiological responses to exercise and to evaluate exercise capacity according to burn severity. METHODS: The study included a total of 64 burn patients, comprising 33 with moderate injuries (Total body surface area: 9.93 +/- 4.73%; mean age: 37 +/- 11.93 years) and 31 with major injuries (Total body surface area: 39.03 +/- 10.36%; mean age: 41.09 +/- 14.96 years). Heart rate, systolic blood pressure, diastolic blood pressure, double product, dyspnea level, oxygen saturation and leg fatigue before and after the shuttle walk test were recorded. Walking distances were measured after the shuttle walk test. RESULTS: A significant difference was determined between patients with major and moderate burn injuries in respect of the cardiovascular responses to the shuttle walk test. Major burn injury patients had a significantly shorter walking distance than the moderate burn injury patients (p < 0.05). CONCLUSIONS: Burn injury severity was seen to affect the functional capacity and cardiovascular responses to the shuttle walk test. Shuttle walk test can be preferred to evaluate moderate and major burn injury patients' functional capacity in the acute period of injury.
Keywords: Burn injury; cardiovascular responses; exercise capacity; shuttle walk test; MYOCARDIAL OXYGEN-CONSUMPTION; SHUTTLE WALK TEST; HEALTHY-SUBJECTS; REFERENCE VALUES; EXERCISE; EPIDEMIOLOGY; CHILDREN; ADULTS